Adolescência, internet e saúde mental: uma revisão de escopo - Bienzobás, Sara Malvez (Universidade Federal de São Carlos, 2021)
According to the literature, the advent of the Internet and virtual social networks have increasingly crossed the daily lives of individuals in general, especially adolescents and, although it already have points to indications of the existence of a relationship between technological modernity, its fruits and the psychosocial development of adolescents, studies that delve into this theme are incipient. Therefore, the objective of the present study was to identify and analyze, by means of a scoping review, studies and reports published in national and international journals that relate adolescent mental health and Internet use. For the project proposal, an active search was carried out in the databases Scopus, Web Of Science and the Virtual Health Library (VHL), using the descriptors: adolesc*, teenage*, young*, social networks, internet, online, mental health and mental suffering, with specific inclusion and exclusion criteria that selected thirty-four articles for the final sample. The treatment and analysis of the results obtained were based on the steps proposed by the Joanna Briggs-JBI Institute for scope reviews and after the analysis of all productions, the results were organized into four distinct thematic categories: 1) Harmful and indiscriminate use of digital social networks; 2) Violence in the virtual environment - Cyberbullying and Cyber Vandalism; 3) The internet as a means of exposure of mental suffering and 4) The internet as a means/space of exposure of mental suffering. It was possible to conclude that little was produced in the national literature, being the international literature the great base for the study. It was found that the adolescent public has become the central target of the reach of the virtual world, and that this generates a direct impact on their daily life, behavior, and relationships, which may cause or aggravate psychological and emotional problems. It was also possible to verify that there is a predominance of the female gender in the harmful use of social networks, and that the virtual environment, as a powerful influencing link, may open a path for the development of early intervention strategies and mental health promotion, as there seems to be a greater tendency related to the exposure of feelings on the internet. This theme has gained strength in recent years, highlighting the growing problem and the need for new productions.
Adolescence, internet and mental health: a scope review
Keywords: Adolescência; Internet; Saúde mental; Redes sociais digitais; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL